Women's entrepreneurship and its role in promoting tourism industry in Algeria - Djrebi, ESSEBTI; Benkhdidja, Moncef; BOUKHDENA, Amina (Milev Journal of Research and Studies, 2022)
The aim of this study is to highlight the role that women entrepreneurs can play in Algeria to develop the tourism industry by establishing institutions in areas that attract Algerian women , The results showed that women’s entrepreneurships more oriented towards the services, crafts and free professions sectors which are more compatible with the specificities and trends of Algerian women. Thus women’s entrepreneurship can be considered real lever for the development of tourism industry in Algeria. To women in Algeria and the tourism provided that they work to develop the entrepreneurial spirit of women through the dissemination of their tourism culture ; while lifting the bureaucratic and financial obstacles before them , and paying more attention